2019
DOI: 10.4317/medoral.22889
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration in diabetic patients. A systematic review

Abstract: Background Oral bone regeneration techniques (OBRT) attempt to provide the appropriate bone volume and density to correctly accomplish dental implant treatments. The objective was to determine whether differences exist in the clinical outcomes of these techniques between diabetic and non-diabetic patients, considering the level of scientific evidence. Material and Methods A systematic review following PRISMA statements was conducted in the PubMed, Scopus and Cochrane da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…Research results report on high percentage (8 to 32%) of reparative osteogenesis disorders in type 2 DM patients and that hyperglycemia leads to decrease of proliferation and differentiation of cartilage and osteoblastic diferon cells involved in regeneration [14][15][16][17]. Our study revealed proliferation and differentiation disorders of osteoblastic diferon towards the formation of fibrocartilage regenerate in animals with CH.…”
Section: Discussionsupporting
confidence: 51%
“…Research results report on high percentage (8 to 32%) of reparative osteogenesis disorders in type 2 DM patients and that hyperglycemia leads to decrease of proliferation and differentiation of cartilage and osteoblastic diferon cells involved in regeneration [14][15][16][17]. Our study revealed proliferation and differentiation disorders of osteoblastic diferon towards the formation of fibrocartilage regenerate in animals with CH.…”
Section: Discussionsupporting
confidence: 51%
“…As reported, mineral homeostasis and osteoid production are significantly decreased in TIIDM patients [ 12 ], which might represent a new target for improving bone quality in patients. Will the scaffold-produced ionic environment modulate the biomineralization process by regulating ion metabolism?…”
Section: Resultsmentioning
confidence: 92%
“…The serum levels of osteocalcin (OCN) are decreased in DM, which alters calcium and phosphate homeostasis [ 10 ] . Additionally, the impairment of parathyroid hormone activity is also observed in DM, which could further induce disordered phosphorus and calcium (Ca–P) metabolism [ 11 , 12 ]. This disordered Ca–P metabolism further results in the alteration of osteo-differentiation into adipo-differentiation and impairs osteogenic differentiation, which inhibits bone regeneration and reduces bone quality and quantity [ 4 , 7 , 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Patients with uncontrolled diabetes frequently experience oral problems affecting the periodontal tissues, calcified tissues, and oral mucosa. 5,8 Studies have shown patients cannot achieve effective plaque control without motivational procedures based on education and information on periodontal diseases and their initiating and etiological factors. 9 Oral health education is a primary defense against periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%